2007
DOI: 10.3141/2019-08
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analysis of Road Safety with Video Data

Abstract: Traffic safety analysis has often been undertaken with historical collision data. However, well-recognized availability and quality problems are associated with collision data. In addition, the use of collision records for safety analysis is reactive: a significant number of collisions has to be recorded before action is taken. Therefore, the observation of traffic conflicts has been advocated as a complementary approach in the analysis of traffic safety. However, incomplete conceptualization and the cost of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 16 publications
0
65
1
2
Order By: Relevance
“…While initial methods were purely qualitative and used only subjective statements to identify and characterise evasive actions of road users in response to conflicts, newer methods have become more quantitative and have provided definitions for measures of the severity of conflicts (18)(19)(20). This has also been facilitated by advances in imaging technology, which now enables the automated observation of sites and application of traffic conflicts techniques is a much simpler way, as opposed to earlier techniques based on manual observation and the use of grading sheets (21)(22). Notable examples of techniques in use today include: the "Swedish Traffic Conflicts Technique" (STCT) from Lund University in Sweden (23), which focuses upon evaluating the time to accident and vehicle speed at the beginning of an evasive action using a graph, which has disaggregating lines to categorise the different conflicts according to severity; the "CIHT Conflicts Technique" (CIHTCT) from the Transport and Road Research Laboratory in the UK (14), which uses a categorisation of the various comprising elements of the conflict and creates levels of severity for each element, such that by summing up the given element levels an overall grading of the severity of the conflict can be obtained; and the "USDoT Conflict Technique" (USDoTCT) from the FHWA in the US (13), which is similar in concept to the CIHTCT but uses different grading criteria.…”
Section: Introductionmentioning
confidence: 99%
“…While initial methods were purely qualitative and used only subjective statements to identify and characterise evasive actions of road users in response to conflicts, newer methods have become more quantitative and have provided definitions for measures of the severity of conflicts (18)(19)(20). This has also been facilitated by advances in imaging technology, which now enables the automated observation of sites and application of traffic conflicts techniques is a much simpler way, as opposed to earlier techniques based on manual observation and the use of grading sheets (21)(22). Notable examples of techniques in use today include: the "Swedish Traffic Conflicts Technique" (STCT) from Lund University in Sweden (23), which focuses upon evaluating the time to accident and vehicle speed at the beginning of an evasive action using a graph, which has disaggregating lines to categorise the different conflicts according to severity; the "CIHT Conflicts Technique" (CIHTCT) from the Transport and Road Research Laboratory in the UK (14), which uses a categorisation of the various comprising elements of the conflict and creates levels of severity for each element, such that by summing up the given element levels an overall grading of the severity of the conflict can be obtained; and the "USDoT Conflict Technique" (USDoTCT) from the FHWA in the US (13), which is similar in concept to the CIHTCT but uses different grading criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the internationally accepted definition of a traffic conflict became (and remains) "an observable situation in which two or more road users approach each other in space and time to such an extent that there is a risk of collision if their movements remain unchanged" (12). This alternative definition has been adopted in a number of safety studies (13)(14)(15)(16)(17). Sayed and Zein developed predictive models that use linear regression analysis to relate the number…”
Section: Past Work Safety-related Issuesmentioning
confidence: 99%
“…In a previous paper (16), the authors have shown that traffic conflicts can be detected in video sequences using HMM-based semisupervised machine learning techniques. This paper presents an extension of the earlier work (16,17): a comprehensive probabilistic framework relying on the concept of the safety hierarchy. It provides a computational definition of severity as the probability of collision that is suited for an automated system.…”
Section: Introductionmentioning
confidence: 99%